Cultural Supernaturalism in Indonesian Horror Films: An Analysis of “Nini Thowok” and Its Reflection of Javanese Folklore (Universitas Pamulang, 2024)
This study explores the role of cultural supernaturalism in Indonesian horror films, focusing on the 2018 film Nini Thowok, which is based on Javanese folklore. The study aims to examine how traditional spiritual beliefs and modern narratives intersect in Indonesian horror, particularly through the symbolism of the nini thowok doll. Using a qualitative approach, the study analyzes the film’s narrative, setting, and characters to uncover the broader cultural themes it represents. The research findings suggest that Nini Thowok not only uses supernatural elements for horror but also reflects the social tensions between tradition and modernization in Indonesia. The film’s depiction of ancestral debt and spiritual responsibility highlights the enduring influence of folklore in modern cinema, offering insight into how these themes resonate with Indonesian audiences. The study concludes that the integration of folklore in Nini Thowok contributes to the global appeal of Indonesian horror films while preserving cultural identity.